(untitled)
Urbanization has a far-reaching impact on the environment, economy, political and social processes. Therefore, understanding the spatial distribution and evolution of human settlements is a key element in planning strategies that ensure the sustainable development of urban and rural settlements. Currently, there is a lack of a comprehensive cartographic image that would show the extent and spatial distribution of both urban and rural settlement in Poland. Accordingly, it is very important to map human settlements and to monitor the development of cities and villages. In this monograph research on this issue is presented. It was associated with, among others, the selection of settlement data, development of data implementation methods and a cartographic method of presenting the settlement network. The basis of the analysis was Global Urban Footprint (GUF) and data register of the National Geodetic and Cartographic Resource (PZGiK). Project included the implementation and harmonization of Global Urban Footprint data and the National Geodetic and Cartographic Resource, including: generalization of GUF raster data using mathematical morphology, conversion of raster data into vector data and intersecting them with PZGiK vector data. The next stage of the analysis was to define and develop an organizational form of the spatial database on settlement network in Poland. The final stage of the analysis was the application of developed methodological assumptions for the presentation of the cartographic settlement map. The adopted assumptions of cartographic visualization enabled the presentation of the full settlement network image against the background of natural conditions in the form of a digital map and an analog map.